2022
DOI: 10.3390/nu14153166
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-Related Risk Factors for Maternal Morbidity during Pregnancy: A Systematic Review

Abstract: Vitamin D has well-defined classical functions related to metabolism and bone health but also has non-classical effects that may influence pregnancy. Maternal morbidity remains a significant health care concern worldwide, despite efforts to improve maternal health. Nutritional deficiencies of vitamin D during pregnancy are related to adverse pregnancy outcomes, but the evidence base is difficult to navigate. The primary purpose of this review is to map the evidence on the effects of deficiencies of vitamin D o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…The journal literature on vitamin D and maternal mortality is relatively limited. However, there is a reasonable body of literature on the role of vitamin D in reducing the risk of adverse pregnancy and birth outcomes for both the developing fetus and mother, e.g., [ 61 ]. The review by Wagner et al [ 62 ] outlines important findings regarding complications, including preterm birth, preeclampsia, and gestational diabetes, as well as adverse effects that appear in early childhood, such as asthma and neurological development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The journal literature on vitamin D and maternal mortality is relatively limited. However, there is a reasonable body of literature on the role of vitamin D in reducing the risk of adverse pregnancy and birth outcomes for both the developing fetus and mother, e.g., [ 61 ]. The review by Wagner et al [ 62 ] outlines important findings regarding complications, including preterm birth, preeclampsia, and gestational diabetes, as well as adverse effects that appear in early childhood, such as asthma and neurological development.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis showed evidence to support vitamin D supplementation as a cost-effective public health strategy to minimize adverse maternal health outcomes. Whenever possible, supplementation should be based on initial vitamin D serum levels with the intent to obtain and maintain optimal levels of a minimum of 40 ng/mL throughout the pregnancy for maximum impact [ 61 ]. In venues where testing is not affordable or convenient, innovative evidence-based technologies such as the Vitamin D Deficiency Risk Assessment Quiz (beta) and the Vitamin D*Calculator can aid providers of prenatal care in assessing individual VDD risk and calculating an individualized evidence-based loading and maintenance doses based on target optimal blood levels of 40 ng/mL, respectively (GrassrootsHealth.net, accessed 15 September 2022) In light of the results of the present review, further studies should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to birthweight, a meta-analysis of three observational studies found a weak positive association between maternal vitamin D status and birthweight after adjusting for potential confounders 44 . In addition, recent reviews suggested that appropriate levels of vitamin D during pregnancy are associated with less morbidity during pregnancy 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was suggested that even higher levels of vitamin D (40–60 ng/mL of 25(OH)D 3 in the serum) are beneficial, reducing the occurrence and severity of multiple types of cancer [ 23 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] and displaying neuroprotective [ 61 ] and cardioprotective properties [ 62 , 63 ]. Consequently, high doses of vitamin D were found to be beneficial in the prevention or treatment of several diseases, including cancer [ 23 , 54 , 56 , 58 , 59 , 64 ], neurodegenerative disorders, autoimmune diseases [ 43 , 45 , 65 , 66 ], psoriasis [ 67 , 68 ], and preeclampsia [ 69 ]. This must be of special interest because vitamin D deficiency is still a global problem [ 21 , 39 , 55 , 70 , 71 , 72 ].…”
Section: Vitamin D—overviewmentioning
confidence: 99%